2016
DOI: 10.3892/ol.2016.4588
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin and protein expression patterns in squamous cell carcinoma of the oral cavity provide evidence for two distinct pathogenetic pathways

Abstract: Squamous cell carcinoma (SCC) of the oral cavity is a morphological heterogeneous disease. Various cytokeratin (CK) expression patterns with different prognostic values have been described, but little is known concerning the underlying biological cell mechanisms. Therefore, the present study investigated 193 cases of oral SCCs using immunohistochemistry for α/β/γ-catenin, glucose transporter 1, caspase-3, X-linked inhibitor of apoptosis protein, hypoxia inducible factor-1α, carbonic anhydrase 9, heat shock pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 44 publications
4
25
0
1
Order By: Relevance
“…In the report of Schwerer et al, cytokeratins CK10 and CK13 typical for squamous differentiation and cytokeratin 20 were negative in all WT specimens and its metaplastic variant . Also, smooth muscle actin (SMA) expressed in myoepithelial cells was not detected in WTs.…”
Section: Wt Immunophenotypementioning
confidence: 94%
See 2 more Smart Citations
“…In the report of Schwerer et al, cytokeratins CK10 and CK13 typical for squamous differentiation and cytokeratin 20 were negative in all WT specimens and its metaplastic variant . Also, smooth muscle actin (SMA) expressed in myoepithelial cells was not detected in WTs.…”
Section: Wt Immunophenotypementioning
confidence: 94%
“…However, in another study, CK10 immunoreactivity was found in five of eight WTs . Immunoreactivity for CK 5/14 and 17, typical of regenerative cells, was restricted to basal cells in WT, and for basal and surface cells in metaplastic WT …”
Section: Wt Immunophenotypementioning
confidence: 97%
See 1 more Smart Citation
“…The cytokeratins are considered to be the largest intermediate filaments of squamous epithelium and are critically important for the stabilization, shape, intracellular communication and transport within the cell. Therefore, cytokeratin expression is of considerable importance in tumor progression (Frohwitter et al, 2016). Based on cytokeratin immunostaining, all of the tumor parenchyma and squamous mucosal epithelial cells were identified as having positive cytoplasmic staining, and the tumor was confirmed to be of epithelial origin.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover recent reports suggest that interactions between keratins and other proteins modulate signaling cascades that regulate cell migration, invasion, and metastasis. According to this suggestion several cytokeratins were found differently expressed in malignant epithelial cells, their specific expression pattern frequently correlated with the prognosis and metastatic potential of certain tumors, like in breast cancer and tumors of the oral cavity [ 24 25 ]. KRT1 is coexpressed with KRT10 in the suprabasal layer of the epidermis, elevated expression of the KRT1/KRT10 complex indicate increased terminal differentiation of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%